The Construction of a Trustworthy Investment Opportunity: Insights from the Madoff Fraud - Stolowy, Hervé; Messner, Martin; Jeanjean, Thomas; Richard Baker, C. (Contemporary Accounting Research, 2014)
In this paper, we use the investment fraud of Bernard Madoff to inquire into the production of trust in the context of financial markets. Drawing upon empirical data related to U.S. individual investors (interviews and letters) as well as documentary material, we investigate the mechanisms through which investing with Madoff came to be seen as a trustworthy investment opportunity. We show how different types of information contributed to construct Bernard Madoff as a trustworthy investment manager and how Madoff avoided meeting demands for accountability by manipulating investors in face-to-face encounters. We shed particular light on the role of institution-based forms of trust which play a critical role in facilitating economic exchanges. More specifically, we suggest that the Madoff case illuminates how the provision of information can lead to an “illusion of trustworthiness” that is difficult to escape for investors. An element of such illusion, we suggest, is inherent to the functioning of financial markets more generally.